Orlistat for obesity management with high levels of TNFα in children - Arya Adi Bramasta; Sri Deasy Aryeni Hadianto; Thio Ceryle Eriady; Michelle Ruth Natalie; Nadya Putri Purwanto (Institute of Computer Science (IOCS), 2023)
Childhood obesity has increased significantly over the past four decades. Obesity is the leading cause of preventable death in the world. An excess of body fat or adiposity characterizes it. TNFα expression in adipose tissue increases during the development of obesity. With the magnitude of the risk caused by obesity, efforts must be carried out to overcome obesity. Orlistat is a drug approved for obesity treatment in adolescents and children by the FDA. The data collection method was collected from articles related to orlistat in obesity management with high levels of TNFα in children. The inclusion criteria were from original articles, case-control studies, and review papers on childhood obesity, TNFα, and orlistat. Orlistat is effective in obesity management with high levels of TNFα in children. Obesity is associated with low-level inflammatory processes in WAT. The increase in adipose tissue mass simultaneously activates inflammatory processes in WAT, located in the liver and immune cells. WAT is the source of several pro-inflammatory cytokines, mainly TNFα. The use of orlistat has been recognized as an effective way to lose weight in childhood obesity. Along with weight loss, a decrease in adipocytes reduces TNF α levels in children.